Analysis of Mathematics Communication Capabilities in Linear Program Problem Solving during the Covid-19 Pandemic - Zeni Fadlila Agustina; Titin Masfingatin; Swasti Maharani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze students' mathematical communication skills orally and in writing in solving linear programming problems during the COVID-19 pandemic. This research uses descriptive qualitative research. The subjects of this study research are two students of class XI MIPA at MAN Ponorogo. Determination of the subject using purposive sampling based on problem-solving tests and interviews. Subject criteria are students who answer most completely and correctly. The research instrument is in the form of problem-solving test questions and interview guidelines. The result of this study is that during the COVID-19 pandemic, learning is carried out online. Students' mathematical communication skills in solving linear programming problems in online learning during the COVID-19 pandemic include being able to express mathematical ideas orally or in writing, being able to compile mathematical models orally or in writing, and being able to write and explain the process of solving mathematical problems verbally or in writing.